Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Tarif Pajak Efektif : Studi Kasus Pada Perusahaan Yang Terdaftar di Jakarta Islamic Index 70 Periode Tahun 2018 – 2023 - Felyna Priyanka; Budi Sukardi (AKUNTANSI 45, 2025)
This study aims to determine how profitability, liquidity and company size affect the effective tax rate in companies listed on the Jakarta Islamic Index 70 / JII70 sharia stock index in 2018 - 2023. The data obtained are secondary data accessed through (www.idx.co.id) with a sampling method of purposive sampling. The data analysis method used is quantitative analysis using descriptive statistics. The results of the study indicate that profitability calculated using return on assets (ROA) has an effect on the effective tax rate. This statement is obtained from the results of the t-test on the profitability variable showing a regression coefficient of 2.990036 and a significance level of 0.0000 and a calculated tvalue> ttable (4.304274> 1.974902). Liquidity calculated using the current ratio shows a regression coefficient of 0.003716 and a significance level of 0.08790 and a calculated tvalue < ttable (0.152506 < 1.974902). Company size shows a regression coefficient of -0.002982 and a significance level of 0.9585 and a calculated tvalue < ttable (-0.52145 < 1.974902). The effect of profitability, liquidity and company size simultaneously/together affects the effective tax rate of companies listed on the Jakarta Islamic Index 70 / JII 70 in 2018 - 2023 because based on the F test, the calculated fvalue> ftable is 5.716263> 2.66182906 with a significance level of 0.0000 < 0.05.